2005
DOI: 10.1103/physrevlett.94.021801
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the DecayΣ+pμ+μ

Abstract: We report the first evidence for the decay Sigma(+)-->pmu(+)mu(-) from data taken by the HyperCP (E871) experiment at Fermilab. Based on three observed events, the branching ratio is B(Sigma(+)-->pmu(+)mu(-))=[8.6(+6.6)(-5.4)(stat)+/-5.5(syst)]x10(-8). The narrow range of dimuon masses may indicate that the decay proceeds via a neutral intermediate state, Sigma(+)-->pP(0),P0-->mu(+)mu(-) with a P0 mass of 214.3+/-0.5 MeV/c(2) and branching ratio B(Sigma(+)-->pP(0),P0-->mu(+)mu(-))=[3.1(+2.4)(-1.9)(stat)+/-1.5(… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 8 publications
6
70
1
Order By: Relevance
“…For example, as the decay AE ! p þ À was observed [2], the authors of Refs. [3,4] studied the contribution from new physics candidates by analyzing the data.…”
Section: Introductionmentioning
confidence: 74%
“…For example, as the decay AE ! p þ À was observed [2], the authors of Refs. [3,4] studied the contribution from new physics candidates by analyzing the data.…”
Section: Introductionmentioning
confidence: 74%
“…A collider search for h → 2a → 4μ was first proposed in [380], which took m a ≈ 215 MeV, as motivated by an excess in HyperCP measurements of Σ þ → pμ þ μ − decay [381]. This study pointed out that modifications of the (then-)standard muon isolation algorithms would be required to preserve the signal and concluded that as long as reasonable efficiencies for muon identification could be maintained, the signal had excellent prospects for detection.…”
Section: B Existing Collider Studiesmentioning
confidence: 99%
“…The quantities pertinent to Σ + → pµ + µ − that have been measured so far are the branching fraction and the dimuon invariant-mass distribution [1,2]. If a good amount of data on this decay become available from future experimental efforts, there are other observables that can be analyzed.…”
Section: Observablesmentioning
confidence: 99%
“…The rare hyperon decay Σ + → pµ + µ − gained much attention in 2005 when the HyperCP Collaboration at Fermilab reported the first evidence for this mode consisting of three events with the same dimuon invariant mass M µµ = 214.3 MeV [1]. Although the implied rate was consistent with its standard model (SM) value, the event clustering hinted at the possibility that the decay was mediated by a light new particle.…”
Section: Introductionmentioning
confidence: 99%